Comparison of two test designs for evaluating the shear bond strength of resin composite cements. Issue 2 (February 2016) - Hu, M.; Weiger, R.; Fischer, J.
Abstract: Objective: To compare a shear bond strength test for resin composite cements developed in order to better consider the shrinkage stress (here termed "Swiss shear test") with the shear test design according to ISO 29022. Method: Four restorative materials (VITA Enamic (VE), VITA Suprinity (VS), Vitablocs Mark II (VM) and VITA YZ T (YZ)) served as substrate. VE, VS and VM were polished or etched. YZ was polished, sandblasted or etched. Specimens were either bonded according to the Swiss or the ISO shear test. RelyX Unicem 2 Automix, Maxcem Elite and PermaFlo DC were used as cements. Shear bond strength (SBS) was measured. Failure modes (adhesive, cohesive or mixed) were evaluated by means of SEM. Results: Mean SBS values obtained with the Swiss shear test were significantly lower than those obtained with the ISO shear test. VE and VM exhibited similar SBS, values of VS were significantly higher. On etched surfaces VM and VE exhibited primarily cohesive failures, VS primarily adhesive failures. On polished substrates significantly lower bond strength values and exclusively adhesive failures were observed. YZ exhibited solely adhesive failures. Compared to polished YZ, SBS significantly increased after sandblasting and even more after etching. Only for adhesively failed specimens mean SBS values of Swiss and ISO shear test were strongly correlated. Significance: Both test designs showed the same ranking of test results. When adhesive failure occurred test results were strongly correlated. When cohesive failure was involved, both test designs did not provide reliable results.